2018
DOI: 10.1002/celc.201800063
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Reaction Activity of Thermally Tailored Nitrogen‐Doped Carbon Electrocatalysts Prepared through Plasma Synthesis

Abstract: Although nitrogen-doped carbon catalysts are promising candidates for oxygen reduction reactions (ORRs), the role of the nitrogen bonding structure, such as pyridinic-N, amino-N, and graphitic-N, on the ORR activity remains controversial. Furthermore, despite recent progress in tuning the CÀN chemical bonding states within the carbon materials by using chemical vapor deposition and post heat treatment, a systematic evaluation of various N moieties remains challenging, owing to the differences in the thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…As displayed in Figure a, Figure S1a and b, Fe‐SA/NCS−X showed the flaky structures with smooth surface. HRTEM image of Fe‐SA/NCS‐700 in Figure b showed the microporous structures whose average diameters were less than 2 nm marked by the light purple circles, and displayed a lamellar spacing of 0.33‐0.34 nm, matching well with the (002) facets of graphitic carbon . Fe‐SA/NCS‐800 and Fe‐SA/NCS‐900 also showed the similar structures, observed in Figure S1c and S1d.…”
Section: Resultsmentioning
confidence: 55%
“…As displayed in Figure a, Figure S1a and b, Fe‐SA/NCS−X showed the flaky structures with smooth surface. HRTEM image of Fe‐SA/NCS‐700 in Figure b showed the microporous structures whose average diameters were less than 2 nm marked by the light purple circles, and displayed a lamellar spacing of 0.33‐0.34 nm, matching well with the (002) facets of graphitic carbon . Fe‐SA/NCS‐800 and Fe‐SA/NCS‐900 also showed the similar structures, observed in Figure S1c and S1d.…”
Section: Resultsmentioning
confidence: 55%
“…Recently, a great deal of research has been reported on the development of a heterogeneous atomic-doped carbon catalyst through bottom-up synthesis using heterocyclic compounds through liquid plasma engineering. The approach has many advantages, such as being conducted at room temperature and being able to synthesize a heterogeneous atomic-doped carbon catalyst simply by selecting different precursors [37][38][39][40][41][42][43][44]. On the other hand, due to the low thermal stability of amino-N, it is hard to retain amino-N on the carbon matrix by the conventional synthesis route [27].…”
Section: Introductionmentioning
confidence: 99%
“…For the one‐step production of NCNPs, the plasma deposition approach and the SP technique are both regarded as effective procedures ( Figure a). [ 123 ] The C–N type can be regulated by the types of additives and precursors (Figure 17b,c). Li and co‐workers fabricated various NCNPs with pyridine and acrylonitrile as precursors and Ru as additives, which can control the content of N elements (Figure 17d–g).…”
Section: Synthesis Of Metal‐free Carbon‐based Orr Catalyst Materials ...mentioning
confidence: 99%
“…Reproduced with permission. [ 123 ] Copyright 2018, Wiley‐VCH. b) Diagram of NCNP synthesis by SP method.…”
Section: Synthesis Of Metal‐free Carbon‐based Orr Catalyst Materials ...mentioning
confidence: 99%